Minimum effective concentration of bupivacaine for axillary brachial plexus block guided by ultrasound - Alexandre Takeda; Leonardo Henrique Cunha Ferraro; André Hosoi Rezende; Eduardo Jun Sadatsune; Luiz Fernando dos Reis Falcão; Maria Angela Tardelli (Revista Brasileira de Anestesiologia, 2015)
INTRODUCTION: The use of ultrasound in regional anesthesia allows reducing the dose of local anesthetic used for peripheral nerve block. The present study was performed to determine the minimum effective concentration (MEC90) of bupivacaine for axillary brachial plexus block. METHODS: Patients undergoing hand surgery were recruited. To estimate the MEC90, a sequential up-down biased coin method of allocation was used. The bupivacaine dose was 5 mL for each nerve (radial, ulnar, median, and musculocutaneous). The initial concentration was 0.35%. This concentration was changed by 0.05% depending on the previous block; a blockade failure resulted in increased concentration for the next patient; in case of success, the next patient could receive or reduction (0.1 probability) or the same concentration (0.9 probability). Surgical anesthesia was defined as driving force ≤2 according to the modified Bromage scale, lack of thermal sensitivity and response to pinprick. Postoperative analgesia was assessed in the recovery room with numeric pain scale and the amount of drugs used within 4 h after the blockade. RESULTS: MEC90 was 0.241% [R 2: 0.978, confidence interval: 0.20-0.34%]. No patient, with successful block, reported pain after 4 h. CONCLUSION: This study demonstrated that ultrasound guided axillary brachial plexus block can be performed with the use of low concentration of local anesthetics, increasing the safety of the procedure. Further studies should be conducted to assess blockade duration at low concentrations.